PENERIMAAN APLIKASI KAMUS ISTILAH AKUNTANSI PADA SMARTPHONE DENGAN METODE UTAUT - Widayati, Qoriani; Panjaitan, Febriyanti (Universitas Bina Darma, 2014)
Social demand for IT-based services technology is very variatif, one of the requirements is for the availability of the dictionary with many kind ranging from general dictionaries such as language dictionaries to the dictionary of specific terms such as politics, economics dictionaries, psychology dictionaries and others. Dictionary of accounting terms are constructed using smartphones more easier using for user.Based on previous research with the title The Design Dictionary of Accounting Terms Smartphone with method Extreme Programming (Usman: 2013) has resulted obstruction dictionary of accounting terms that can be viewed using a Smartphone in www.kamusistilahakuntansi.org. As the follow-up from the previous research in this research study will doing an analysis of the vocabulary terms using the method of accounting the Unified Theory of Acceptance and Use of Technology (UTAUT).